EVALUASI MUTU MINUMAN PROBIOTIK AIR KELAPA MUDA DAN SARI BUAH NAGA MERAH MENGGUNAKAN LACTOBACILLUS FERMENTUM INACC B1295 - Syafri Ajrin; Usman Pato; Rahmayuni (Fakultas Pertanian Universitas Riau, 2023)
The purpose of this study was to determine the best ratio of coconut water and red dragon fruit juice for making probiotic drink by utilizing Lactobacillus fermentum InaCC B1295. This research was conducted experimentally using a completely randomized design with five treatments and four replications. This study compared coconut water and red dragon fruit juice, specifically P1 (100:0), P2 (90:10), P3 (80:20), P4 (70:30) and P5 (60:40). The experimental parameters in this study consisted of acidity degree, titratable accidity, total LAB, fat level, and sensory characteristics. The data obtained were analyzed statistically by analysis of variance using IBM SPSS 23 Duncan’s New Multiple Range Test at level 5%. The results showed that addition of red dragon fruit juice with different ratio significantly affected the chemical, microbiological, physical and organoleptic assessment of probiotic drinks. The best treatment is P3 treatment (ratio of coconut water and red dragon fruit juice 80:20) with the criteria of 4.91 pH value, 0.66% titratable accidity, 8.93 log CFU/ml total LAB, and 0.81% fat level. Characteristics for descriptive sensory test of the P3 treatment showed slightly purplish red color, typical flavorful fermentation, rather sour and less homogeneous.